AN EMPIRICAL RESEARCH FOR MULTI-DIRECTIONAL EVALUATION OF THE RELATIONSHIP OF COMPETITION AND INNOVATION DIMENSIONS: G20 GROUP COUNTRIES EXAMPLE - ALTINTAŞ, Furkan Fahri (Business & Management Studies: An International Journal, 2020)
1. LITERATURE 1.1. RESEARCH SUBJECT According to many quantitative studies, it has been concluded that innovation and competition dimensions have a mutually positive and significant relationship with each other because the relationship between innovation and competition has a dynamic feature (Aytürkmen and Aynaoğlu, 2018). In the rapidly increasing competitive environment, products and services that are differentiated, have added value and make it easier to meet needs, always stick. Thus, countries that attach importance to innovation will be able to achieve competitive advantage by obtaining economic and added value. Also, innovation plays a crucial role in competitiveness. In a competitive environment, countries need new skills, methods and technologies to dominate the competitive process (Cantwell, 2003; Clark & Guy, 2010). In this context, the subject of the research is to explain the relationship structure between innovation and competition dimensions according to quantitative data. 1.2. RESEARCH PURPOSE AND IMPORTANCE The first aim of the study is to determine the relationship between the dimensions of competition and innovation, the contribution values of the indicators of the dimensions, the canonical relationship between the dimensions and the dimension that contributes more to the relationship with the dimension within the framework of a heterogeneous structure. The second aim of the study is to determine the contribution values of the indicators to the dimensions relationship. This dimension contributes more to the relationship between dimensions, and how the indicators are classified as influencing or affected in the holistic relationship within the framework of a heterogeneous and homogeneous structure. When the national and international literature is scanned, no research has been found that measures the relationship between competition and innovation within the data of the components that make up the global competition and innovation index of G20 countries for 2018 and 2019. In this context, this research is the first study in the literature that complies with the specified features. 1.3. CONTRIBUTION of the ARTICLE to the LITERATURE This research is a data set for those who want to investigate the relationships between competition and innovation in multiple ways. Also, this research can provide discussion and causality analysis of these relational structures within the scope of multi-faceted determination of relational structures in the formation of relationships between competition and innovation dimensions in terms of method. Besides, this research becomes a method study on how to determine inter-dimensional relationships only as heterogeneous, heterogeneous and homogeneous. Therefore, this study is thought to fill this gap in the literature. 2. DESIGN AND METHOD 2.1. RESEARCH TYPE The study is a research article within the scope of evaluating the relationships between competition and innovation dimensions from different aspects, taking into account the values of the indicators that determine the global innovation and global competition index of the G20 countries. 2.2. RESEARCH PROBLEMS The problem of the study is to determine the relationship structure between the indicators of innovation and competition dimensions as homogeneous and homogeneous-heterogeneous, based on the values of the indicators that determine the global innovation and global competition index of the G20 countries. 2.3. DATA COLLECTION METHOD The data of the research constitute the quantitative values of the indicators that make up the global innovation and competitiveness index of the G20 group countries within the scope of 2018 and 2019. The data of these countries are prepared by the global innovation index in a report by Cornell University, INSEAD and WIPO institutions every year. In this context, the innovation data of the countries subject to the study were obtained from the website www.globalinnovationindex.org. The global competition index for 2018 and 2019 was prepared by Klaus Schwab and the World Economic Forum. Accordingly, competition data of the countries have been obtained from the website https://reports.weforum.org/. 2.4. QUANTITATIVE / QUALITATIVE ANALYSIS Within the scope of the first aim of the study, the Pearson correlation coefficient, Somer's d effect coefficient and canonical correlations were used to determine the heterogeneous relationship structure between indicators of competition and innovation dimensions. Within the scope of the second purpose of the research, the DEMATEL numerical method was used to determine the structure of the homogeneous and heterogeneous relationship between indicators of competition and innovation dimensions. 3. FINDINGS AND DISCUSSION 3.1. FINDINGS as a RESULT of ANALYSIS Within the scope of the heterogeneous relationship, the first three relationship states that contribute to the relationship structure between competition and innovation dimensions and close to a very high degree of relationship are Kre4 (innovation ecosystem) and Gkie3 (infrastructure), Kre4 (innovation ecosystem) and Gkie2 (human capital and research), respectively. Kre2 (human capital) and Gkie3 (infrastructure). Again, within the scope of the heterogeneous relationship, the first three indicators that contribute the most to the relational structure between the dimension of competition and innovation are respectively Gkie3 (infrastructure), Gkie2 (human capital and research) and Kre4 (innovation ecosystem). In general terms, within the scope of the heterogeneous relationship, the innovation dimension contributed more to the relational structure with the competitive dimension than the competition dimension Within the scope of the homogeneous and heterogeneous relationship, the first three indicators that contribute to the relational structure the most are Gkie3 (infrastructure), Kre4 (innovation ecosystem) and Gkie2 (human capital and research), respectively. Again, in general terms, within the scope of the homogeneous-heterogeneous relationship, the competitive dimension has contributed more to the relational structure with the innovation dimension than the innovation dimension. 3.2. DISCUSSING the FINDINGS with the LITERATURE In this study, the relationship between innovation and competition dimensions was positive and meaningful by the results of most studies found in the literature. Besides, the research was similar to the studies of Aynaoğlu (2018) and Ay Türkmen and Aynaoğlu (2017) in determining the relationships between countries' global innovation index and global competitiveness index indicators. 4. CONCLUSION, RECOMMENDATION AND LIMITATIONS 4.1. RESULTS of the ARTICLE According to the findings, the innovation dimension in terms of heterogeneous relationship and the competition dimension in terms of homogeneous-heterogeneous relationship contributed more to the relational structure between competition and innovation dimensions. 4.2. SUGGESTIONS BASED on RESULTS In this context, according to the findings of the G20 countries, it was found that only the relationships between Kre1 (Enabling Environment) and Çkie2 (Creative Output) indicators were not significant and were very weak. Accordingly, G20 countries should carry out activities that complement each other of the indicators of these dimensions in order further to increase the performance of competition and innovation dimensions. In general, all countries around the world should take measures to keep the level of complementarity among indicators of competition and innovation dimensions high. In this context, countries should focus on issues that are related to each other of the indicators of these dimensions. For researchers, within the scope of the suggestion, variables that determine the competition and innovation index of countries can be increased more comprehensively, or country-specific components can be created. In this way, the relationship between competition and innovation can be evaluated as healthier under the components that their countries are currently interested in, affected or affected by. Accordingly, innovation and competition methods and strategies can be determined better in the following periods. 4.3. LIMITATIONS of the ARTICLE The data set of the research was composed of the values of the components that make up the competition and innovation index of the countries for 2018 and 2019. Index values before 2018 were not included in the study. Because in 2018, changes were made in the number and quality of indicators that make up the global competition index. Therefore, the index values of 2018 and 2019 were taken into consideration in order to ensure the consistency of the index values of the countries every year and to provide the research with updated data.